Optimal sample size for assessing bacterioneuston structural diversity - Medeiros, José António Amaro Correia (2013)
The surface microlayer (SML) is located at the interface atmospherehydrosphere and is theoretically defined as the top millimeter of the water column. However, the SML is operationally defined according to the sampling method used and the thickness varies with weather conditions and organic matter content, among other factors. The SML is a very dynamic compartment of the water column involved in the process of transport of materials between the hydrosphere and the atmosphere. Bacterial communities inhabiting the SML (bacterioneuston) are expected to be adapted to the particular SML environment which is characterized by physical and chemical stress associated to surface tension, high exposure to solar radiation and accumulation of hydrophobic compounds, some of which pollutants. However, the small volumes of SML water obtained with the different sampling methods reported in the literature, make the sampling procedure laborious and time-consuming. Sample size becomes even more critical when microcosm experiments are designed. The objective of this work was to determine the smallest sample size that could be used to assess bacterioneuston diversity by culture independent methods without compromising representativeness and therefore ecological significance. For that, two extraction methods were tested on samples of 0,5 mL, 5 mL and 10 mL of natural SML obtained at the estuarine system Ria de Aveiro. After DNA extraction, community structure was assessed by DGGE profiling of rRNA gene sequences. The CTAB-extraction procedure was selected as the most efficient extraction method and was later used with larger samples (1 mL, 20 mL and 50 mL). The DNA obtained was once more analyzed by DGGE and the results showed that the estimated diversity of the communities does not increase proportionally with increasing sample size and that a good estimate of the structural diversity of bacterioneuston communities can be obtained with very small samples.